The supporting role of Trans-European energy networks to the Turkish accession process - Muñoz Delgado, Beatriz; San Martín González, Enrique (Papeles de Europa, 2010)
Turkey is participating in a number of projects included in the list of Trans-European Energy Networks. Turkey's energy infrastructure has gradually grown in importance, as the accession process has progressed, culminating in the opening of the Trans- European Networks chapter in December 2007, which was recognition of the country’s level of harmonization on the subject. The specific feature in this area is that what is at stake for the EU is rather more than a candidate country’s simply transposing the acquis communautaire. The issue is the participation and involvement of a country which is geostrategically crucial to Europe’s energy routes, and a country which can make a substantial contribution to the diversification and security of the EU's energy supplies. Thus, this extra value represents a key factor in favor of Turkey's integration. If the EU wants to count on Turkey in this endeavour it needs to keep it duly committed and provide it with adequate incentives. For Turkey this means fulfilling its aspirations of full membership. The issue is that these two processes seem to be running at a different pace and to different timescales, making it probable that, in the medium term, the accession process will continue to be delayed, while the development of Turkey's energy infrastructure presses ahead. However, in the long term, the outcome of the accession process will be the determining factor for the EU's energy issues and network projects.
Keywords: European Union; Turkey; Energy policy; Energy security; Energy infrastructures; EU’s enlargement policy